Association between erythritol and lung cancer: a two-sample Mendelian randomization study. - Zhao, Yongsheng; Zheng, Renyan; Luo, Kexin; Zhao, Haiyang; Xiang, Wanping (Nutrition & Metabolism, 2025)
Background: Sweeteners have been widely added to food and beverages due to their low-calorie and sweetening properties. However, the role of sweeteners in cancer risk has been a subject of extensive debate over the past few decades. Objective: We aimed to elucidate the causation between the commonly used natural sweetener erythritol and the risk of lung cancer (LC) using Mendelian randomization (MR). Methods: Data on erythritol and its metabolites were obtained from publicly available genome-wide association studies data. Summary data on LC and its subtypes were obtained from a large-scale genetic study conducted by the Transdisciplinary Research of Cancer in Lung of the International Lung Cancer Consortium and the Lung Cancer Cohort Consortium. We conducted independent two-sample MR analyses to assess the causation between erythritol and LC and its subtypes. Results: The inverse variance weighted method of MR analysis showed no evidence supporting causation between erythritol and LC or its histological subtypes. Sensitivity analysis further supported the results. Conclusion: Our study findings do not support genetic association between erythritol and LC or its subtypes.